The Geometry of Golden Conjugate Connections - Blaga, Adara M. (Sarajevo Journal of Mathematics, 2024)
Properties of Golden conjugate connections are stated by pointing out their relation to product conjugate connections. We define the analogues in Golden geometry of the structural and the virtual tensors from the almost product geometry and express the Golden conjugate connections in terms of these tensors. 2010 Mathematics Subject Classification. 53C07, 53C15, 53C25.